Myśląc o wieloetniczności - Wojdon, Joanna (Centrum Edukacji Obywatelskiej, 2018)
The book uses the Bix Six Historical Thinking Concepts developed by Peter Seixas (University of British Columbia): analysing causes and consequences, identifying continuity and change, using primary source evidence, establishing historical significance, taking historical perspectives and understanding ethical dimensions of history. Six lesson scenarios have been developed that promote the concepts and present methods of historical research. The content is based on the results of the interneational research project „Mechanisms of cohesion building of multiethnic societies, 10th-21st c.” coordinated by Przemysław Wiszewski of the University of Wrocław.
Keywords: history education; historical thinking; inquiry-based history learning; multiethnic societies in history education; medieval European history in education; history lessons